HOMECARE SERVICES’ POTENTIAL AT THE UMM HOSPITAL: ANALYSIS ON THE DISEASE CASES, PUBLIC SOCIAL AND ECONOMY - Prasetyo, Yoyok Bekti (University of Muhammadiyah Malang, 2016)
Limitations of the community to pay for health services in cases of degenerative diseases requires a relatively long treatment, thus impacting the ever increasing cases that require follow-up nursing home. This study aims to identify the public health problems which need at service homecare, identify the assets required to service homecare, selecting issues problems with depth analysis of the problem characteristics homecare, define service needs homecare terminology measurable factors include economy and social, formulate design service model homecare (services inside the building and outside the building). Observational method is used in this research. The results of the study identified health issues that have the potential to do homecare is wound care, antenatal care, clean cord care, palliative cases. The model of homecare services need to be developed in the form of discharge planning in RS UMM